Effects Of Pigeon PEA (Cajanus Cajan) Consumption to Decrease Blood Pressure on Elderly Hypertension in the Region of Barana Health Center of Jeneponto (Medico Legal Update, 2021)
Hypertension is a high-risk condition that causes of deaths, stroke, and coronary heart disease. This studyaims to determinethe effect of giving pigeon pea (Cajanus cajan) baruasa on systolic and diastolic bloodpressure of elderly with hypertension.The research is quasy experimental design with pre-post test group. A total of 36 elderly people withhypertension were divided into intervention group and control group by random sampling. Data wereanalyzed using Mann-Whitney and Wilcoxon with 95% confidence level.The results of this study indicate that: There is an effect giving pigeon pea (Cajanus cajan) baruasa on thesystolic blood pressure of elderly with hypertension (p = 0.001